Pengaruh Kepemilikan Jaminan Kesehatan Masyarakat Miskin terhadap Status Kelahiran dan Kejadian Stunting pada Baduta Indonesia (Analisis Data IFLS 1993 – 2007) - Demsa Simbolon (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background. One of the policies to address health and nutrition issues is Health Insurance Program for the Poor (ASKESKIN) imposed by the Decree of the Minister of Health of the Republic of Indonesia number 1241/MENKES/SK/XI/2004 as mandated by National Social Security System. However, coverage is still low, which is expected to have an impact on the birth status and nutritional status of children under-two years old. Objective. To prove that membership of a health insurance for the poor (ASKESKIN) has effect on birth status and the incidence of stunting of children under-two years old in Indonesia. Method. The research is using the positivist paradigm, the data is analysed using cross- sectional study based on Indonesian Family Life Survey (IFLS) in 1993-2007. The samples were all children under two years who were randomly netted in IFLS1 (1993) until IFLS4 (2007), with inclusion criteria biological children, living with parents, single live birth and birth, the data available on birth weight, gestational age, anthropometry. Univariate, bivariate and logistic regression mutivariat using 3 sets of data to identify the effect of health insurance ownership to birth weight (n = 3956), gestational age (n = 4998) and the incidence of stunting (n = 4504). Results. Ownership of health insurance affects LBW, preterm and stunting. Children under two years old from family that have health insurance other than ASKESKIN are protected from LBW (OR, 95 % CI = 0.61; 0.43 to 0.88). However, there was no difference risk of LBW among children under two years old from families with ASKESKIN and those without any health insurance. (OR, 95 % CI = 0.92; 0.52 to 1.61) (model 1). Children from ASKESKIN family has a risk factor for the prevalence of preterm (OR, 95 % CI: 1.74; 1.14 to 2.66) (model 2). Children from families that have health insurance other than ASKESKIN are protected from stunting (OR, 95 % CI = 0.78, 0.62 to 0.98), but there is no difference in risk of stunting among children from families with ASKESKIN compared to children from famililies that do not have health insurance (OR, 95 % CI = 1.01; 0.69 to 1.47) (model 3). Conclusion. Policy makers need to evaluate the Community Health Insurance Program (ASEKSKIN). The Maternal Children Health and Nutrition intervention was done with less emphasis on promotive and preventive efforts. People utilize curative measures only when problems occur in relation to the health and nutrition of mothers and children. Latar belakang. Salah satu kebijakan untuk mengatasi masalah kesehatan dan gizi adalah Program Jaminan Pemeliharaan Kesehatan bagi Masyarakat Miskin (PJKMM) yang diberlakukan dengan Surat Keputusan Menteri Kesehatan Republik Indonesia (SK Menkes RI) No. 1241/Menkes/SK/XI/ 2004 sebagai amanat UU No. 40/2004 tentang Sistem Jaminan Sosial Nasional (SJSN). Namun cakupannya masih rendah, yang diperkirakan berdampak pada masih tingginya masalah riwayat kelahiran dan status gizi baduta. Tujuan. Membuktikan pengaruh kepemilikan jaminan kesehatan masyarakat miskin terhadap status kelahiran dan kejadian stunting baduta Indonesia. Metode. Penelitian menggunakan paradigma positivist dengan pendekatan crossectional study berdasarkan data Indonesia Family Life Survey (IFLS) tahun 1993-2007. Sampel adalah seluruh bayi dan baduta yang secara random terjaring dalam IFLS1 (1993) sampai IFLS4 (2007), dengan kriteria inklusi anak kandung, tinggal dengan orang tua, lahir hidup dan lahir tunggal, tersedia data berat lahir, umur kehamilan, antropometri. Analisis univariat, bivariat dan regresi logistik mutivariat menggunakan 3 set data untuk mengidentifikasi pengaruh kepemilikan Jaminan kesehatan terhadap berat lahir (n=3956), umur kehamilan (n=4998) dan kejadian stunting (n=4504). Hasil. Kepemilikan jaminan kesehatan berpengaruh terhadap BBLR, prematur dan stunting. Bayi dari keluarga peserta jaminan kesehatan Non-ASKESKIN terproteksi dari BBLR (OR;95% CI= 0,61; 0,43-0,88). Namun tidak ada perbedaan risiko BBLR antara bayi dari keluarga peserta Askeskin dan yang tidak memiliki jaminan kesehatan (OR;95% CI =0,92; 0,52-1,61) (model 1). Kepemilikan ASKESKIN sebagai faktor risiko kejadian prematur (OR, 95% CI: 1,74; 1,14-2,66) (model 2). Anak dari keluarga peserta jaminan kesehatan Non-ASKESKIN terproteksi dari kejadian stunting (OR;95% CI =0,78; 0,62-0,98), namun tidak ada perbedaan risiko stunting antara anak dari keluarga peserta ASKESKIN dengan anak dari keluarga yang tidak memiliki jaminan kesehatan (OR;95% CI =1,01; 0,69-1,47) (model 3). Kesimpulan. Penentu kebijakan perlu melakukan evaluasi pada program Jaminan Kesehatan Masyarakat (keluarga miskin), karena intervensi KIA dan Gizi yang dilakuan kurang menekankan pada upaya promotif dan prefentif, sehingga utilisasi masyarakat lebih pada upaya kuratif bila terjadi masalah Kesehatan dan Gizi pada ibu dan anak.